Experimental and theoretical study of the ablation of silicon with THz bursts of fs laser pulses - Gaudiuso, Caterina; Terekhin, Pavel N.; Volpe, Annalisa; Nolte, Stefan; Rethfeld, Baerbel; Ancona, Antonio (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
We report on an experimental and theoretical investigation on the laser ablation of silicon with THz bursts of fs pulses. Craters were generated by varying the burst features, i.e., the number of pulses and the intra-burst repetition rate, and compared to those obtained in Normal Pulse Mode (NPM). A general reduction of the thermal load was observed using bursts, though with a lower ablation rate. In fact, shallower craters were obtained when increasing the number of pulses and reducing the intra-burst repetition rates at fixed processing time and burst energy. However, for bursts at 2 THz, some combinations of process parameters allowed a higher specific ablation rate compared to NPM. Simulations based on the numerical solution of the density-dependent two temperature model showed that bursts with more pulses or with lower intra-burst repetition rates lead to a lower final temperature, thus supporting the experimental findings. This is ascribed to changes of the reflectivity dependent on the number of pulses. Accordingly, different amounts of energy are transferred from the laser pulse to the sample, which also leads to changes in specific ablation rates. The origin of such a behavior was found to be the non-linear absorption processes, especially the two-photon absorption.
CRIS-Team Scopus Importer:2023-04-20